Wear-resistant easy-to-decontaminate luggage fabric and processing method thereof
By applying wear-resistant antibacterial decontamination modification liquid to the wear-resistant base cloth layer of the bag fabric, the problem of insufficient anti-fouling performance and antibacterial properties of the existing fabric is solved, and higher wear resistance, stain removal and antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411565535.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing luggage fabrics have shortcomings in anti-fouling performance and antibacterial properties, which are difficult to meet consumers' needs for wear resistance, easy decontamination and antibacteriality.
A wear-resistant base cloth layer consisting of polyester fiber, cotton fiber and bamboo fiber is used, and the surface is coated with wear-resistant and antibacterial detergent modification liquid to form a wear-resistant and easy-to-dirty bag fabric. The modification solution is rich in active hydroxyl groups, trifluoromethyl groups, catechol groups, pyridyl groups and disulfide bonds, improving the wear resistance, stain removal and antibacterial properties of the fabric.
It significantly improves the wear resistance, stain removal and antibacterial properties of bag fabrics, making them easier to clean and maintain and extend their service life.
Smart Images

Figure BDA0005119128950000311 
Figure BDA0005119128950000312 
Figure BDA0005119128950000321
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luggage fabric manufacturing, and in particular relates to a wear-resistant and easily decontaminated luggage fabric and a processing method thereof. Background Art
[0002] Bags are essential equipment in daily life, used to store and carry items. As consumers' requirements for the quality and functionality of bags continue to increase, the fabrics used to make bags have evolved from traditional leather to polyester, nylon and Oxford cloth. The materials of bag fabrics are mainly textile fabrics (including Oxford cloth, nylon, canvas, etc.), leather (natural leather, artificial turf, synthetic leather, etc.) and other materials.
[0003] At present, cloth-based bags and leather bags are the most commonly used bag fabrics. Cloth-based bags have the advantages of being light, soft, breathable and comfortable to wear. Natural leather bags have the advantages of being breathable, sweat-absorbent, comfortable, easy to protect and strong. Synthetic leather sports shoes have the advantages of being strong, waterproof and warm. It can be seen that only artificial leather sports shoes are waterproof, stain-resistant and easy to clean, while cloth sports shoes have poor stain resistance and are not easy to clean after being stained.
[0004] Therefore, in order to improve the wearing experience, developing a luggage fabric with good wear resistance, strong stain removal performance and strong antibacterial performance is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant base fabric layer is woven from the following fibers by weight: 60-64 parts of polyester fiber, 24-32 parts of cotton fiber and 16-22 parts of bamboo fiber; the wear-resistant antibacterial surface layer is obtained by coating a wear-resistant antibacterial decontamination modifying liquid on the surface of the wear-resistant base fabric layer;
[0007] The preparation method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0008] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer;
[0009] Step S2, preparing a primary finished product: coating the wear-resistant, antibacterial, and decontamination-modifying liquid through a coating machine, controlling the coating temperature to be 150-160° C., and maintaining the coating machine speed at 25-35 yards per minute. After coating a layer, drying is performed, and the process is repeated 2-4 times to obtain a primary finished product;
[0010] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0011] Preferably, the total coating thickness of the wear-resistant and antibacterial decontamination modifying liquid is 0.6-0.8 mm.
[0012] Preferably, in step S1, the count of the warp yarn is 10-12s, the count of the weft yarn is 14-16s, and the weaving process parameters are: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%.
[0013] Preferably, the method for preparing the wear-resistant and antibacterial decontamination modifying liquid comprises the following steps:
[0014] Step A1, adding 2-amino-1,3-benzenediol to anhydrous DMF, heating to 45-55°C, stirring evenly, adjusting the pH to 9-10, and dropping a mixed solution a of allyl glycidyl ether and isopropanol while stirring, and controlling the dropping to be completed within 30 minutes. After the dropping is completed, heating to 74-80°C, continuing to stir and react for 6-10 hours, adjusting the pH to neutral, rotary evaporation, washing and drying to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and the mixed solution a is 2-4:50-60:16, and the mass ratio of allyl glycidyl ether to isopropanol in the mixed solution a is 1.9-3.7:12. In the above reaction process, using anhydrous DMF as solvent, the amino group on the amino monomer undergoes a ring-opening esterification reaction with allyl glycidyl ether to obtain the trihydroxy monomer;
[0015] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring evenly, heating to 75-85° C. under nitrogen protection, stirring for reaction for 18-20 hours, standing for 4-6 hours after the reaction, filtering, washing, and drying to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2-4.4:1.0-1.4:0.04-0.06:45-65, in the above reaction process, using anhydrous DMF as solvent and p-toluenesulfonic acid as catalyst, the trihydroxy monomer and 2-amino-3-(trifluoromethyl)benzoic acid undergo esterification reaction to obtain a wear-resistant decontamination monomer, in the above reaction process, the amount of trihydroxy monomer is controlled to be slightly higher than 3,5-diaminobenzoic acid, so that after the reaction is completed, there are still remaining hydroxyl groups that can undergo subsequent reactions;
[0016] Step A3, adding fluorinated monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring evenly, then adding 4,4'-dithiodibutyric acid, heating to 64-72°C, stirring for 6-10h, cooling to room temperature after the reaction, filtering, washing and drying the filter cake to obtain a wear-resistant decontamination monomer, wherein the fluorinated monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid The mass ratio is 3.4-4.6:2.4-3.6:1.8-2.4:45-65:2.6-3.4, anhydrous DMF is used as solvent, dicyclohexylcarbodiimide is used as dehydrating agent, 4-dimethylaminopyridine is used as catalyst, the amino group of the fluorine-containing monomer and the carboxyl group on 4,4'-dithiodibutyric acid undergo amidation reaction to obtain a wear-resistant decontamination monomer, and in the above reaction process, the amount of 4,4'-dithiodibutyric acid is controlled to be slightly higher than that of the fluorine-containing monomer;
[0017] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are mixed until uniform, the temperature is raised to 70-80°C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, and the reaction is continued for 1.6-2.2 hours to obtain a prepolymer; the temperature is raised to 80-90°C, the prepolymer is added to polyethylene glycol, and then the dihydroxyl silicone oil and the wear-resistant decontamination monomer are added, and the reaction is stirred for 1.8-2.6 hours, and the temperature is lowered to 62-68°C, and then the functionalized particles and the photoinitiator are added, and the mixture is stirred uniformly, and ultraviolet light is irradiated for 10-20 minutes. Deionized water is added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol, double-terminated hydroxyl silicone oil, wear-resistant and decontamination monomer, functionalized particles, photoinitiator and deionized water is 10.6-12.4: 50-60: 52-64: 48-56: 0.32-0.68: 47-54: 61-73: 12-14: 3.6-4.8: 0.04-0.05: 360-420.
[0018] Preferably, in step A4, the photoinitiator is dimethyl benzoate.
[0019] Preferably, the method for preparing the functionalized particles comprises the following steps:
[0020] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, heated to 35-45 ° C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, stirred evenly, and then heated to 110-130 ° C, stirred for 8-12 hours, after the reaction is completed, cooled to room temperature, centrifuged, washed and dried to obtain modified nano titanium dioxide, and then added to cyclohexane, stirred until uniform, adjusted the pH value to 8.5-9.5, and then added octadecyl trimethoxysilane, heated to 56-62 ° C, continued to stir for 4-6 hours, after the reaction is completed, adjusted the pH to The invention relates to a novel nano-titanium dioxide preparation method, wherein the modified nano-titanium dioxide is prepared by a LSS method, and then the modified nano-titanium dioxide is coated with octadecyltrimethoxysilane as a silicon source to obtain the wear-resistant decontamination particles. The modified nano-titanium dioxide is prepared by a LSS method, and then the modified nano-titanium dioxide is coated with octadecyltrimethoxysilane as a silicon source to obtain the wear-resistant decontamination particles.
[0021] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, heat to 40-60 ° C, continue stirring for 5-7h, centrifuge, wash and dry to obtain epoxy wear-resistant decontamination particles, add the epoxy wear-resistant decontamination particles to anhydrous DMF, stir evenly, drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF mixed solution b, after the addition is completed, heat to 90-110 ° C, stir and react for 2-3h, after the reaction is completed, centrifuge and precipitate, wash and dry to obtain functionalized particles; wherein the wear-resistant decontamination particles, deionized water, anhydrous ethanol The mass ratio of alcohol and KH-560 is 2-4:10-12:20-28:0.12-0.24, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and mixed solution b is 4:40-50:12, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.1:0.32-0.46:10. The wear-resistant decontamination particles are first treated with KH-560 to obtain epoxy wear-resistant decontamination particles, and then under the action of tetrabutylammonium bromide, the carboxyl group of 2-mercaptonicotinic acid and the epoxy group undergo a ring-opening reaction to obtain functionalized particles.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In order to improve the wear resistance, detergency and antibacterial properties of luggage fabrics, the present invention coats the surface of the prepared wear-resistant base fabric layer with a wear-resistant antibacterial decontamination modifying liquid containing wear-resistant decontamination monomers and functionalized particles. The wear-resistant decontamination monomers are rich in active hydroxyl groups, trifluoromethyl groups, catechol groups, pyridyl groups and disulfide bonds. On the one hand, the active hydroxyl groups can form hydrogen bonds with the active hydroxyl groups on the surface of the wear-resistant base fabric layer to strengthen the binding force between molecules and improve the wear resistance of the luggage fabric. On the other hand, as anchor points, the active hydroxyl groups react with the epoxy groups of the functionalized particles to further increase the degree of crosslinking and improve the wear resistance of the luggage fabric. The trifluoromethyl group has a lower surface energy and can improve the decontamination performance of the luggage fabric. The presence of the catechol group and the pyridyl group can exert the rigidity of their own molecules and improve the wear resistance of the luggage fabric. On the other hand, the catechol group and the pyridyl group both have good antibacterial properties and can improve the antibacterial properties of the luggage fabric. The presence of the dynamic disulfide bond can improve the self-repairing performance of the wear-resistant antibacterial decontamination modifying liquid, and further The present invention further improves the wear resistance of luggage fabrics. The functionalized particles are composed of a core-shell structure. The outer layer is an amino silica structure containing a flexible alkyl long chain and a modified silica structure obtained by a ring-opening reaction of 2-mercaptonicotinic acid. The inner core is modified nano-titanium dioxide. The existence of the modified silica structure, on the one hand, has good wear resistance itself. On the other hand, the flexible alkyl long chain grafted thereon has good flexibility and fluidity, can reduce the adhesion and accumulation of dyes, and has good antifouling property. The pyridine group has a rigid structure with good wear resistance and good antibacterial property. The existence of modified nano-titanium dioxide, on the one hand, exerts the photocatalytic properties of nano-titanium dioxide and thus improves the antifouling property of the fabric. On the other hand, the dodecyl dimethyl hydroxypropyl sulfobetaine molecules attached to the nano-titanium dioxide can not only improve the dispersibility and compatibility of the nano-titanium dioxide, but also have good antibacterial ability. Introducing it into the wear-resistant and antibacterial decontamination modification liquid can work synergistically with the wear-resistant and decontamination monomer to jointly improve the wear resistance, decontamination and antibacterial properties of the luggage fabrics. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The contents of the main raw materials and their components used in the examples and comparative examples are as follows:
[0026] The polyethylene glycol is polyethylene glycol 400 produced by Jinan Jiayang Chemical Co., Ltd., with a CAS number of 25322-68-3; the double-terminal hydroxy silicone oil is double-terminal hydroxy silicone oil IOTA 2110 produced by Anhui IOTA Silicone Oil Co., Ltd., with an active content of 99% and a molecular weight of 2000; the polyetheramine D-230 was purchased from Aladdin Reagents online.
[0027] Preparation Examples 1-3 and Comparative Preparation Examples 1-3 provide a method for preparing functionalized particles.
[0028] Preparation Example 1
[0029] This preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0030] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, the temperature is raised to 35°C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, the speed is controlled to 550rpm, stirring for 25min until uniform, then the temperature is raised to 110°C, the speed is maintained unchanged, and the stirring reaction is continued for 8h. After the reaction is completed, it is cooled to room temperature, centrifuged and precipitated, and then washed three times with a mass fraction of 30% ethanol aqueous solution, dried at 50°C to constant weight, and modified nano titanium dioxide is obtained, and then added to cyclohexane, the speed is controlled to be 1200rpm and stirred for 12min until uniform, and 0.6M hydrogen The pH value of the aqueous sodium hydroxide solution was adjusted to 8.5, and then octadecyltrimethoxysilane was added, the temperature was raised to 56°C, and stirring was continued for 4 hours. After the reaction was completed, the pH was adjusted to neutral with a 0.4M hydrochloric acid aqueous solution, centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and dodecyl dimethyl hydroxypropyl sulfobetaine was 2:20:60:0.1, and the mass ratio of modified nano titanium dioxide, cyclohexane, and octadecyltrimethoxysilane was 3:60:0.26;
[0031] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 0.5h, heat to 40°C, control the speed to 600rpm and stir for 5h, centrifuge and precipitate, then wash with anhydrous ethanol and deionized water 3 times in sequence, dry at 55°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles. Add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 700rpm and stir for 30min until uniform, and drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF. After the addition of F mixed solution b is completed, the temperature is raised to 90°C, the rotation speed is maintained unchanged, and the reaction is stirred for 2 hours. After the reaction is completed, the precipitation is centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 65°C to constant weight to obtain functionalized particles, wherein the mass ratio of wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 is 2:10:20:0.12, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and mixed solution b is 4:40:12, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.1:0.32:10.
[0032] Preparation Example 2
[0033] This preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0034] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, the temperature is raised to 40°C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, the speed is controlled to 600 rpm, stirring for 20 min until uniform, then the temperature is raised to 120°C, the speed is maintained unchanged, and the stirring reaction is continued for 10 h. After the reaction is completed, it is cooled to room temperature, centrifuged and precipitated, and then washed 4 times with a mass fraction of 35% ethanol aqueous solution, and dried at 55°C to constant weight to obtain modified nano titanium dioxide, which is then added to cyclohexane, stirred at a speed of 1300 rpm for 10 min until uniform, and 0.8 M hydroxide is used. The pH value was adjusted to 8.5 with a sodium chloride aqueous solution, and then octadecyltrimethoxysilane was added, the temperature was raised to 59°C, and stirring was continued for 5 hours. After the reaction was completed, the pH was adjusted to neutral with a 0.6M hydrochloric acid aqueous solution, centrifuged, and then washed with anhydrous ethanol and deionized water for 4 times in sequence, and dried at 70°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and dodecyldimethylhydroxypropylsulfobetaine was 3.5:30:64:0.15, and the mass ratio of modified nano titanium dioxide, cyclohexane, and octadecyltrimethoxysilane was 4:70:0.28;
[0035] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, control the ultrasonic frequency to 35kHz, the ultrasonic power to 550w, ultrasonic for 0.6h, heat to 50°C, control the speed to 650rpm and stir for 6h, centrifuge and precipitate, then wash with anhydrous ethanol and deionized water 4 times in sequence, dry at 60°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles, add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 750rpm and stir for 25min until uniform, and drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF After the addition of the mixed solution b was completed, the temperature was raised to 100°C, the rotation speed was maintained unchanged, and the reaction was stirred for 2.5 hours. After the reaction was completed, the mixture was centrifuged and precipitated. The mixture was then washed four times with anhydrous ethanol and deionized water, and dried at 70°C to constant weight to obtain functionalized particles, wherein the mass ratio of wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 was 3:11:24:0.18, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and the mixed solution b was 4:45:12, and the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF in the mixed solution b was 0.1:0.39:10.
[0036] Preparation Example 3
[0037] This preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0038] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, heated to 45°C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, the speed is controlled to 650rpm, stirring for 15min until uniform, then heated to 130°C, the speed is maintained unchanged, stirring and reacting for 12h, after the reaction is completed, cooled to room temperature, centrifuged and precipitated, then washed 5 times with 35% ethanol aqueous solution, dried at 60°C to constant weight, to obtain modified nano titanium dioxide, then added to cyclohexane, stirred at 1400rpm for 8min until uniform, and 1. 0M sodium hydroxide aqueous solution to adjust the pH value to 9.0, then add octadecyltrimethoxysilane, heat to 62°C, continue stirring for 6 hours, after the reaction is completed, adjust the pH to neutral with 0.8M hydrochloric acid aqueous solution, then wash with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 75°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and dodecyl dimethyl hydroxypropyl sulfobetaine is 5:40:68:0.2, and the mass ratio of modified nano titanium dioxide, cyclohexane and octadecyltrimethoxysilane is 5:80:0.30;
[0039] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 for 30 minutes, heat to 60°C, continue stirring for 7 hours, centrifuge and precipitate, wash with anhydrous ethanol and deionized water 5 times in sequence, dry at 65°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles. Add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 800rpm and stir for 20 minutes until uniform, add tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF mixed solution b dropwise, and after the addition is completed, heat to The reaction was stirred at 110°C for 3 hours. After the reaction was completed, the particles were centrifuged and washed with anhydrous ethanol and deionized water for 5 times, respectively. The particles were dried at 75°C to constant weight to obtain functionalized particles. The mass ratio of the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 was 4:12:28:0.24, the mass ratio of the epoxy wear-resistant decontamination particles, anhydrous DMF and the mixed solution b was 4:50:12, and the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF in the mixed solution b was 0.1:0.46:10.
[0040] Comparative Preparation Example 1
[0041] This comparative preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0042] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, heated to 35°C, sodium dodecyl sulfate is added while stirring, the speed is controlled to 550rpm, and stirring is continued for 25min until uniform, and then the temperature is raised to 110°C, the speed is maintained unchanged, and the stirring reaction is continued for 8h. After the reaction is completed, it is cooled to room temperature, centrifuged and precipitated, and then washed three times with a mass fraction of 30% ethanol aqueous solution, and dried at 50°C to constant weight to obtain modified nano titanium dioxide, which is then added to cyclohexane, and the speed is controlled to be stirred for 12min at 1200rpm until uniform, and 0.6M hydrogen The pH value of the aqueous sodium hydroxide solution was adjusted to 8.5, and then octadecyltrimethoxysilane was added, the temperature was raised to 56°C, and stirring was continued for 4 hours. After the reaction was completed, the pH was adjusted to neutral with a 0.4M hydrochloric acid aqueous solution, centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and sodium dodecyl sulfate was 2:20:60:0.1, and the mass ratio of modified nano titanium dioxide, cyclohexane, and octadecyltrimethoxysilane was 3:60:0.26;
[0043] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 0.5h, heat to 40°C, control the speed to 600rpm and stir for 5h, centrifuge and precipitate, then wash with anhydrous ethanol and deionized water 3 times in sequence, dry at 55°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles. Add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 700rpm and stir for 30min until uniform, and drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF. After the addition of F mixed solution b is completed, the temperature is raised to 90°C, the rotation speed is maintained unchanged, and the reaction is stirred for 2 hours. After the reaction is completed, the precipitation is centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 65°C to constant weight to obtain functionalized particles, wherein the mass ratio of wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 is 2:10:20:0.12, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and mixed solution b is 4:40:12, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.1:0.32:10.
[0044] Comparative Preparation Example 2
[0045] This comparative preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0046] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, the temperature is raised to 35°C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, the speed is controlled to 550rpm, stirring for 25min until uniform, then the temperature is raised to 110°C, the speed is maintained unchanged, and the stirring reaction is continued for 8h. After the reaction is completed, it is cooled to room temperature, centrifuged and precipitated, and then washed three times with a mass fraction of 30% ethanol aqueous solution, and dried at 50°C to constant weight to obtain modified nano titanium dioxide, which is then added to cyclohexane, stirred at a speed of 1200rpm for 12min until uniform, and 0 .6M sodium hydroxide aqueous solution was used to adjust the pH value to 8.5, and then tetramethoxysilane was added, the temperature was raised to 56°C, and stirring was continued for 4 hours. After the reaction was completed, the pH was adjusted to neutral with 0.4M hydrochloric acid aqueous solution, centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and dodecyl dimethyl hydroxypropyl sulfobetaine was 2:20:60:0.1, and the mass ratio of modified nano titanium dioxide, cyclohexane, and tetramethoxysilane was 3:60:0.26;
[0047] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 0.5h, heat to 40°C, control the speed to 600rpm and stir for 5h, centrifuge and precipitate, then wash with anhydrous ethanol and deionized water 3 times in sequence, dry at 55°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles. Add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 700rpm and stir for 30min until uniform, and drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF. After the addition of F mixed solution b is completed, the temperature is raised to 90°C, the rotation speed is maintained unchanged, and the reaction is stirred for 2 hours. After the reaction is completed, the precipitation is centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 65°C to constant weight to obtain functionalized particles, wherein the mass ratio of wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 is 2:10:20:0.12, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and mixed solution b is 4:40:12, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.1:0.32:10.
[0048] Comparative Preparation Example 3
[0049] This comparative preparation example provides a method for preparing functionalized particles, comprising the following steps:
[0050] Step B1, titanium chloride and deionized water are added to anhydrous ethanol, the temperature is raised to 35°C, dodecyl dimethyl hydroxypropyl sulfobetaine is added while stirring, the speed is controlled to 550rpm, stirring for 25min until uniform, then the temperature is raised to 110°C, the speed is maintained unchanged, and the stirring reaction is continued for 8h. After the reaction is completed, it is cooled to room temperature, centrifuged and precipitated, and then washed three times with a mass fraction of 30% ethanol aqueous solution, dried at 50°C to constant weight, and modified nano titanium dioxide is obtained, and then added to cyclohexane, the speed is controlled to be 1200rpm and stirred for 12min until uniform, and 0.6M hydrogen The pH value of the aqueous sodium hydroxide solution was adjusted to 8.5, and then octadecyltrimethoxysilane was added, the temperature was raised to 56°C, and stirring was continued for 4 hours. After the reaction was completed, the pH was adjusted to neutral with a 0.4M hydrochloric acid aqueous solution, centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain wear-resistant decontamination particles, wherein the mass ratio of titanium chloride, deionized water, anhydrous ethanol, and dodecyl dimethyl hydroxypropyl sulfobetaine was 2:20:60:0.1, and the mass ratio of modified nano titanium dioxide, cyclohexane, and octadecyltrimethoxysilane was 3:60:0.26;
[0051] Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 0.5h, heat to 40°C, control the speed to 600rpm and stir for 5h, centrifuge and precipitate, then wash with anhydrous ethanol and deionized water 3 times in sequence, dry at 55°C to constant weight, and obtain epoxy-based wear-resistant decontamination particles. Add the epoxy-based wear-resistant decontamination particles to anhydrous DMF, control the speed to 700rpm and stir for 30min until uniform, and drop tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous DMF. After the addition of F mixed solution b is completed, the temperature is raised to 90°C, the rotation speed is maintained unchanged, and the reaction is stirred for 2 hours. After the reaction is completed, the precipitation is centrifuged, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 65°C to constant weight to obtain functionalized particles, wherein the mass ratio of wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 is 2:10:20:0.12, the mass ratio of epoxy wear-resistant decontamination particles, anhydrous DMF and mixed solution b is 4:40:12, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous DMF is 0.1:0.32:10.
[0052] Preparation Examples 4-6 and Comparative Preparation Examples 4-8 provide a method for preparing a wear-resistant, antibacterial, and decontamination-modifying liquid.
[0053] Preparation Example 4
[0054] This preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0055] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0056] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0057] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4:2.4:1.8:45:2.6;
[0058] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 minutes until uniform, the temperature is raised to 70°C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80°C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the stirring reaction is carried out for 1.8 hours, the temperature is lowered to 62°C, and the functionalized particles prepared in Preparation Example 1 and benzoin dimethyl ether are added, the speed is maintained unchanged, and stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0059] Preparation Example 5
[0060] This preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0061] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 50°C, control the speed to 650rpm and stir for 25min until uniform, adjust the pH to 9.5 with 1.0M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 77°C, maintain the speed unchanged, continue to stir and react for 8h, adjust the pH to neutral with 0.7M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 84°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water 4 times in sequence, and dry at 60°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 3:55:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 2.8:12;
[0062] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 18 min at a controlled speed of 800 rpm until uniform, heating to 80° C. under nitrogen protection, stirring and reacting for 19 h, standing for 5 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 4 times, and drying at 65° C. to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.8:1.2:0.05:55;
[0063] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 25 minutes at a controlled speed of 700 rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 68°C, stirring for 8 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 4 times, and drying at 70°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4-4.6:3.05:2.1:55:3.0;
[0064] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1200 rpm for 14 min until uniform, the temperature is raised to 75 ° C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is reduced to 550 rpm, and the stirring reaction is continued for 1.9 hours to obtain a prepolymer; the temperature is raised to 85 ° C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 650 rpm, the reaction is stirred for 2.2 hours, the temperature is lowered to 66 ° C, and the functionalized particles prepared in Preparation Example 2 and benzoin dimethyl ether are added, the speed is maintained unchanged, and the stirring is continued for 25 minutes until uniform, and then placed at a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 15 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 11.5:55:58:52:0.50:50.5:67:13:4.2:0.045:390.
[0065] Preparation Example 6
[0066] This preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0067] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 55°C, control the speed to 700rpm and stir for 20min until uniform, adjust the pH to 10 with 1.2M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 80°C, continue to stir and react for 10h, adjust the pH to neutral with 0.8M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 86°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 65°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 4:60:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 3.7:12;
[0068] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 12 min at a controlled speed of 900 rpm until uniform, heating to 85° C. under nitrogen protection, stirring and reacting for 20 h, standing for 6 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 5 times, and drying at 70° C. to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 4.4:1.4:0.06:65;
[0069] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 20 minutes at a controlled speed of 750 rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 72°C, stirring for 10 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 5 times, and drying at 75°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 4.6:3.6:2.4:65:3.4;
[0070] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1400 rpm for 12 min until uniform, the temperature is raised to 80 ° C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is reduced to 600 rpm, and the stirring reaction is continued for 2.2 hours to obtain a prepolymer; the temperature is raised to 90 ° C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 700 rpm, the reaction is stirred for 2.6 hours, the temperature is reduced to 68 ° C, and the functionalized particles prepared in Preparation Example 3 and benzoin dimethyl ether are added, the speed is maintained unchanged, and the stirring is continued for 20 minutes until uniform, and then placed at a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 20 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 12.4:60:64:56:0.68:54:73:14:4.8:0.05:420.
[0071] Comparative Preparation Example 4
[0072] This comparative preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0073] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0074] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0075] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4:2.4:1.8:45:2.6;
[0076] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 min until uniform, the temperature is raised to 70 ° C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80 ° C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the reaction is stirred for 1.8 hours, the temperature is lowered to 62 ° C, and the functionalized particles prepared in Comparative Preparation Example 1 and benzoin dimethyl ether are added, the speed is maintained unchanged, and the stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0077] Comparative Preparation Example 5
[0078] This comparative preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0079] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0080] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0081] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4:2.4:1.8:45:2.6;
[0082] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 min until uniform, the temperature is raised to 70 ° C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80 ° C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the reaction is stirred for 1.8 hours, the temperature is lowered to 62 ° C, and the functionalized particles prepared in Comparative Preparation Example 2 and benzoin dimethyl ether are added, the speed is maintained unchanged, and stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminated hydroxyl silicone oil, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0083] Comparative Preparation Example 6
[0084] This comparative preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0085] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0086] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0087] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4:2.4:1.8:45:2.6;
[0088] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 min until uniform, the temperature is raised to 70 ° C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80 ° C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the reaction is stirred for 1.8 hours, the temperature is lowered to 62 ° C, and the functionalized particles prepared in Comparative Preparation Example 3 and benzoin dimethyl ether are added, the speed is maintained unchanged, and the stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0089] Comparative Preparation Example 7
[0090] This comparative preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0091] Step A1, add aniline to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of aniline, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0092] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0093] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650rpm until uniform, then adding 4,4'-dithiodibutyric acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4:2.4:1.8:45:2.6;
[0094] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 minutes until uniform, the temperature is raised to 70°C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80°C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the stirring reaction is carried out for 1.8 hours, the temperature is lowered to 62°C, and the functionalized particles prepared in Preparation Example 1 and benzoin dimethyl ether are added, the speed is maintained unchanged, and stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0095] Comparative Preparation Example 8
[0096] This comparative preparation example provides a method for preparing a wear-resistant and antibacterial decontamination modifying liquid, comprising the following steps:
[0097] Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45°C, control the speed to 600rpm and stir for 30min until uniform, adjust the pH to 9 with 0.8M sodium hydroxide aqueous solution, add a mixture of allyl glycidyl ether and isopropanol dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 74°C, maintain the speed unchanged, continue to stir and react for 6h, adjust the pH to neutral with 0.6M hydrochloric acid aqueous solution, control the rotary evaporation temperature to 82°C, rotary evaporation to remove anhydrous DMF, then wash with anhydrous ethanol and deionized water for 3 times in sequence, and dry at 55°C to constant weight to obtain a trihydroxy monomer, wherein the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2:50:16, and the mass ratio of allyl glycidyl ether and isopropanol in the mixed solution a is 1.9:12;
[0098] Step A2, adding trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring for 24 min at a controlled speed of 700 rpm until uniform, heating to 75°C under nitrogen protection, stirring and reacting for 18 h, standing for 4 h after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 60°C to constant weight to obtain a fluorine-containing monomer, wherein the mass ratio of trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2:1.0:0.04:45;
[0099] Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring for 30 minutes at a controlled speed of 650 rpm until uniform, then adding succinic acid, heating to 64°C, stirring for 6 hours, cooling to room temperature after the reaction, filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain a wear-resistant decontamination monomer, wherein the mass ratio of fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and succinic acid is 3.4:2.4:1.8:45:2.6;
[0100] Step A4, isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate are stirred at a speed of 1000 rpm for 16 minutes until uniform, the temperature is raised to 70°C, polyetheramine D-230 and dibutyltin dilaurate are added while stirring, the speed is increased to 500 rpm, and the stirring reaction is continued for 1.6 hours to obtain a prepolymer; the temperature is raised to 80°C, the prepolymer is added to polyethylene glycol 400, and then the double-terminal alcohol hydroxy silicone oil IOTA 2110 and the wear-resistant decontamination monomer are added, the speed is controlled to 600 rpm, the stirring reaction is carried out for 1.8 hours, the temperature is lowered to 62°C, and the functionalized particles prepared in Preparation Example 1 and benzoin dimethyl ether are added, the speed is maintained unchanged, and stirring is continued for 30 minutes until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was irradiated under ultraviolet light for 10 min, and deionized water was added to obtain a wear-resistant, antibacterial and decontamination modified liquid, wherein the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol 400, double-terminal alcohol hydroxy silicone oil IOTA 2110, wear-resistant and decontamination monomer, functionalized particles, benzoin dimethyl ether and deionized water was 10.6:50:52:48:0.32:47:61:12:3.6:0.04:360.
[0101] Examples 1-3 and Comparative Examples 1-5 provide a wear-resistant and easily decontaminated luggage fabric and a processing method thereof.
[0102] Example 1
[0103] The present embodiment provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in Preparation Example 4 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0104] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0105] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0106] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Preparation Example 4 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0107] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0108] Example 2
[0109] The present embodiment provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in Preparation Example 5 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 62 parts of polyester fiber, 28 parts of cotton fiber and 19 parts of bamboo fiber;
[0110] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0111] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 11s, the weft yarn count is 15s, and the weaving process parameters are controlled as follows: total warp yarn count is 8100, upper machine width is 180cm, upper machine warp density is 370 yarns / 10cm, upper machine weft density is 328 yarns / 10cm, reed number is 51, insertion number is 2 / reed, finished product width is 124cm, lower machine warp density is 350 yarns / 10cm, lower machine weft density is 330 yarns / 10cm, warp shrinkage is 4.7%, and weft shrinkage is 6.2%;
[0112] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Preparation Example 5 is coated by a coating machine, the coating temperature is controlled to be 155° C., the speed of the coating machine is maintained at 30 yards per minute, and the total coating thickness is controlled to be 0.7 mm. After coating a layer, it is placed at 70° C. and baked for 1.5 hours, and repeated 3 times to obtain a primary finished product;
[0113] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0114] Example 3
[0115] The present embodiment provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in Preparation Example 6 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 64 parts of polyester fiber, 32 parts of cotton fiber and 22 parts of bamboo fiber;
[0116] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0117] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 12s, the weft yarn count is 16s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0118] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Preparation Example 6 is coated by a coating machine, the coating temperature is controlled to be 160° C., the speed of the coating machine is maintained at 35 yards per minute, and the total coating thickness is controlled to be 0.8 mm. After coating a layer, it is placed at 75° C. and baked for 1 hour, and repeated 4 times to obtain a primary finished product;
[0119] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0120] Comparative Example 1
[0121] This comparative example provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in comparative preparation example 4 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0122] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0123] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0124] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Comparative Preparation Example 4 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0125] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0126] Comparative Example 2
[0127] This comparative example provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in comparative preparation example 5 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0128] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0129] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0130] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Comparative Preparation Example 5 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0131] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0132] Comparative Example 3
[0133] This comparative example provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in comparative preparation example 6 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0134] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0135] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0136] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Comparative Preparation Example 6 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0137] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0138] Comparative Example 4
[0139] This comparative example provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in comparative preparation example 7 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0140] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0141] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0142] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Comparative Preparation Example 7 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0143] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0144] Comparative Example 5
[0145] This comparative example provides a wear-resistant and easy-to-decontaminate luggage fabric, comprising a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant antibacterial surface layer is obtained by coating the wear-resistant antibacterial decontamination modifying liquid prepared in comparative preparation example 8 on the surface of the wear-resistant base fabric layer; the wear-resistant base fabric layer is woven from the following fibers in parts by weight: 60 parts of polyester fiber, 24 parts of cotton fiber and 16 parts of bamboo fiber;
[0146] The processing method of the wear-resistant and easy-to-decontaminate luggage fabric comprises the following steps:
[0147] Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer, wherein the warp yarn count is 10s, the weft yarn count is 14s, and the weaving process parameters are controlled as follows: total warp number 8100, upper machine width 180cm, upper machine warp density 370 yarns / 10cm, upper machine weft density 328 yarns / 10cm, reed number 51, insertion number 2 / reed, finished product width 124cm, lower machine warp density 350 yarns / 10cm, lower machine weft density 330 yarns / 10cm, warp shrinkage 4.7%, weft shrinkage 6.2%;
[0148] Step S2, preparing a primary finished product: the wear-resistant, antibacterial, and decontamination-modifying liquid prepared in Comparative Preparation Example 8 is coated by a coating machine, the coating temperature is controlled to be 150° C., the speed of the coating machine is maintained at 25 yards per minute, and the total coating thickness is controlled to be 0.6 mm. After coating a layer, it is placed at 65° C. and baked for 2 hours, and repeated twice to obtain a primary finished product;
[0149] Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
[0150] Performance Testing
[0151] The following performance tests were performed on the bag fabrics prepared in Examples 1-3 and Comparative Examples 1-5:
[0152] Wear resistance: The total number of frictions when the luggage fabrics prepared in Examples 1-3 and Comparative Examples 1-5 were damaged was tested by the test method of "BT 21196.2-2007 Determination of the wear resistance of textiles by the Martindale method Part 2 Determination of sample damage". The greater the total number of frictions, the more wear-resistant the shoe and luggage fabrics are;
[0153] Stain resistance: According to the liquid stain method and solid stain method in "B / T 30159.1-2013 Testing and Evaluation of Antifouling Performance of Textiles Part 1: Stain Resistance", the test and classification are carried out respectively. The higher the grade, the better the stain resistance. The liquid stain grade description is shown in Table 1. The solid stain method uses a gray scale for color change to evaluate the color difference between the central part of the stained area and the slightly stained area of the test. When the color difference grade is 3-4 or above, the sample is considered to be resistant to solid stains.
[0154] Antibacterial rate: According to the national standard B / T20944.2-2007 "Evaluation of antibacterial properties of textiles Part 2: Absorption method", the antibacterial quantitative test was carried out, and the antibacterial performance after 100 washings was compared. The washing method was based on B / T8629-2001 "Household washing and drying procedures for textile testing" using a type B agitator washing machine and washing procedure 8B. The specific performance test results are shown in Table 1 below:
[0155] Table 1 Liquid contamination levels
[0156]
[0157] Table 2 Performance test of wear-resistant and easy-to-decontaminate luggage fabrics prepared in Examples 1-3 and Comparative Examples 1-5
[0158]
[0159]
[0160] From the data shown in Table 1 above, it can be seen that the luggage fabrics produced in Examples 1-3 of the present application have higher friction resistance and better stain resistance, and after 100 washes, the antibacterial rates of Staphylococcus aureus and Escherichia coli can still reach more than 97%, which is higher than the national standard evaluation index for antibacterial performance and has excellent antibacterial effect.
[0161] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0162] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A wear-resistant and easy-to-decontaminate luggage fabric, characterized in that: It includes a wear-resistant base fabric layer and a wear-resistant antibacterial surface layer; the wear-resistant base fabric layer is woven from the following fibers by weight: 60-64 parts of polyester fiber, 24-32 parts of cotton fiber and 16-22 parts of bamboo fiber; The wear-resistant and antibacterial surface layer is obtained by coating the wear-resistant and antibacterial decontamination modifying liquid on the surface of the wear-resistant base fabric layer; The preparation method of the wear-resistant and antibacterial decontamination modifying liquid comprises the following steps: Step A1, add 2-amino-1,3-benzenediol to anhydrous DMF, heat to 45-55°C, stir evenly, adjust the pH to 9-10, and dropwise add a mixture of allyl glycidyl ether and isopropanol while stirring, and control the dripping to be completed within 30 minutes. After the dripping is completed, heat to 74-80°C, continue stirring and reacting for 6-10 hours, adjust the pH to neutral, rotary evaporate, wash and dry to obtain a trihydroxy monomer; Step A2, add trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid and p-toluenesulfonic acid to anhydrous DMF, stir evenly, raise the temperature to 75-85° C. under nitrogen protection, stir and react for 18-20 hours, after the reaction is completed, stand for 4-6 hours, filter, wash and dry to obtain a fluorine-containing monomer; Step A3, adding fluorine-containing monomer, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, stirring evenly, then adding 4,4'-dithiodibutyric acid, heating to 64-72°C, stirring for 6-10h, cooling to room temperature after the reaction, filtering by suction, washing and drying the filter cake to obtain a wear-resistant decontamination monomer; Step A4, mix isophorone diisocyanate, ethylene glycol ethyl ether acetate and butyl acetate until uniform, heat to 70-80°C, add polyetheramine D-230 and dibutyltin dilaurate while stirring, continue stirring and reacting for 1.6-2.2h to obtain a prepolymer; heat to 80-90°C, add the prepolymer to polyethylene glycol, then add dihydroxyl silicone oil and wear-resistant decontamination monomer, stir and react for 1.8-2.6h, cool to 62-68°C, add functionalized particles and photoinitiator, stir evenly, irradiate with ultraviolet light for 10-20min, add deionized water, and obtain a wear-resistant, antibacterial and decontamination modified liquid.
2. The wear-resistant and easy-to-decontaminate luggage fabric according to claim 1, characterized in that: In the step A1, the mass ratio of 2-amino-1,3-benzenediol, anhydrous DMF and mixed solution a is 2-4:50-60:16, and in the mixed solution a, the mass ratio of allyl glycidyl ether and isopropanol is 1.9-3.7:
12.
3. The wear-resistant and easy-to-decontaminate luggage fabric according to claim 1, characterized in that: In the step A2, the mass ratio of the trihydroxy monomer, 2-amino-3-(trifluoromethyl)benzoic acid, p-toluenesulfonic acid and anhydrous DMF is 3.2-4.4: 1.0-1.4: 0.04-0.06: 45-65.
4. The wear-resistant and easy-to-decontaminate luggage fabric according to claim 1, characterized in that: In the step A3, the mass ratio of the fluorine-containing monomer, dicyclohexylcarbodiimide, 4-dimethylaminopyridine, anhydrous DMF and 4,4'-dithiodibutyric acid is 3.4-4.6: 2.4-3.6: 1.8-2.4: 45-65: 2.6-3.
4.
5. The wear-resistant and easy-to-decontaminate luggage fabric according to claim 1, characterized in that: In the step A4, the mass ratio of isophorone diisocyanate, ethylene glycol ethyl ether acetate, butyl acetate, polyetheramine D-230, dibutyltin dilaurate, polyethylene glycol, bihydroxyl silicone oil, wear-resistant decontamination monomer, functionalized particles, photoinitiator and deionized water is 10.6-12.4: 50-60: 52-64: 48-56: 0.32-0.68: 47-54: 61-73: 12-14: 3.6-4.8: 0.04-0.05: 360-420.
6. The wear-resistant and easy-to-decontaminate luggage fabric according to claim 1, characterized in that: The method for preparing the functionalized particles comprises the following steps: Step B1, adding titanium chloride and deionized water to anhydrous ethanol, heating to 35-45°C, adding dodecyl dimethyl hydroxypropyl sulfobetaine while stirring, stirring evenly, then heating to 110-130°C, stirring and reacting for 8-12h, after the reaction is completed, cooling to room temperature, centrifuging, washing and drying to obtain modified nano titanium dioxide, then adding it to cyclohexane, stirring until uniform, adjusting the pH value to 8.5-9.5, then adding octadecyl trimethoxysilane, heating to 56-62°C, continuing to stir for 4-6h, after the reaction is completed, adjusting the pH to neutral, centrifuging, washing and drying to obtain wear-resistant decontamination particles; Step B2, ultrasonically mix the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560, heat to 40-60°C, continue stirring for 5-7h, centrifuge, wash and dry to obtain epoxy wear-resistant decontamination particles, add the epoxy wear-resistant decontamination particles to anhydrous DMF, stir evenly, drop tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF mixed solution b, after the addition is completed, heat to 90-110°C, stir to react for 2-3h, after the reaction is completed, centrifuge to precipitate, wash and dry to obtain functionalized particles.
7. The wear-resistant and easily decontaminated luggage fabric according to claim 6, characterized in that: In the step B1, the mass ratio of titanium chloride, deionized water, anhydrous ethanol and dodecyl dimethyl hydroxypropyl sulfobetaine is 2-5:20-40:60-68:0.1-0.2, and the mass ratio of modified nano titanium dioxide, cyclohexane and octadecyl trimethoxysilane is 3-5:60-80:0.26-0.
30.
8. The wear-resistant and easily decontaminated luggage fabric according to claim 6, characterized in that: In the step B2, the mass ratio of the wear-resistant decontamination particles, deionized water, anhydrous ethanol and KH-560 is 2-4:10-12:20-28:0.12-0.24, and the mass ratio of the epoxy-based wear-resistant decontamination particles, anhydrous DMF and the mixed solution b is 4:40-50:
12.
9. The wear-resistant and easily decontaminated luggage fabric according to claim 6, characterized in that: In the mixed solution b, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.1:0.32-0.46:
10.
10. A method for processing the wear-resistant and easily decontaminated luggage fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, preparing a wear-resistant base fabric layer: processing polyester fiber to obtain warp yarn, blending cotton fiber and bamboo fiber to obtain weft yarn, using 2 / 1 twill weave, weaving the warp yarn and the weft yarn to obtain a wear-resistant base fabric layer; Step S2, preparing a primary finished product: coating the wear-resistant antibacterial decontamination modifying liquid on the wear-resistant base fabric layer through a coating machine, controlling the coating temperature to be 150-160° C., and maintaining the speed of the coating machine at 25-35 yards per minute. After coating one layer, drying is performed, and the process is repeated 2-4 times to obtain a primary finished product; Step S3, preparing luggage fabrics: the primary finished product prepared in step S2 is subjected to quality inspection, and if the inspection meets the requirements, it is packaged and put into storage, thereby obtaining wear-resistant and easy-to-decontaminate luggage fabrics.
Citation Information
Cited By
High-toughness glass fiber and preparation method thereof
CN120398437A